Improvements in Upper Extremity Function Following Intensive Training Are Independent of Corticospinal Tract Organization in Children With Unilateral Spastic Cerebral Palsy: A Clinical Randomized Trial - Friel, Kathleen M.; Ferre, Claudio L.; Brandao, Marina; Kuo, Hsing-Ching; Chin, Karen; Hung, Ya-Ching; Robert, Maxime T.; Flamand, Veronique H.; Smorenburg, Ana; Bleyenheuft, Yannick; Carmel, Jason B.; Campos, Talita; et al. (Frontiers in Neurology, 2021)
Background/Objectives: Intensive training of the more affected upper extremity (UE) has been shown to be effective for children with unilateral spastic cerebral palsy (USCP). Two types of UE training have been particularly successful: Constraint-Induced Movement Therapy (CIMT) and Bimanual training. Reorganization of the corticospinal tract (CST) early during development often occurs in USCP. Prior studies have suggested that children with an ipsilateral CST controlling the affected UE may improve less following CIMT than children with a contralateral CST. We tested the hypothesis that improvements in UE function after intensive training depend on CST laterality. Study Design: Randomized clinical trial (https://clinicaltrials.gov: NCT02918890) Study Participants & Setting: 82 children with USCP, age 5 years 10 months to 17 years, university laboratory setting. Materials/Methods: Single-pulse transcranial magnetic stimulation (TMS) was used to determine each child’s CST connectivity pattern. Children were stratified by age, sex, baseline hand function and CST connectivity pattern and randomized to receive either CIMT or Bimanual training, each of which were provided in a day-camp setting (90 hours). Hand function was tested before, immediately and 6 months after the intervention with the Jebsen-Taylor Test of Hand Function, the Assisting Hand Assessment, the Box and Block Test, and ABILHAND-Kids. The Canadian Occupational Performance Measure was used to track goal achievement and the Pediatric Evaluation of Disability Inventory was used to assess functioning in daily living activities at home. Results: In contrast to our hypothesis, participants had statistically similar improvements for both CIMT and Bimanual training for all measures independent of their CST connectivity pattern (contralateral, ipsilateral, or bilateral)(p<0.05 in all cases). Conclusions/Significance: The efficacy of CIMT and Bimanual training is independent of CST connectivity pattern. Children with an ipsilateral CST, previously thought to be maladaptive, have the capacity to improve as well as children with a contralateral or bilateral CST following intensive CIMT or Bimanual training.